Organização espacial e morfologia da cidade de Rubiataba-Goiás - Silva, Uhallas Cordeiro (2017)
Starting from the concept of urban space, it is understood the articulation existing in the spatial organization of the city of Rubiataba, seeking to analyze how they establish the relations between their parts, with the purpose of systematizing this space. The main objective will be to analyze the formation and configuration of the urban space of the city of Rubiataba through its socio-spatial dynamics, in order to understand the logic of the existing relationships in this urban space as to its particularities. Having as a starting point the idea of ​​articulating parts within the urban space, seeking to understand this set of relations, each part (sector) of the city should be characterized by analyzing its form and functionality, in which this analysis will result in the comprehension of the totality of this space urban. The methodological procedures of the research were based on review and bibliographical reading, and a survey of articles, dissertations and theses on medium and small cities was also carried out in the proposal to ascertain the methodologies related to the topic. A survey of official data concerning the service institutions, the productive infrastructure, the demographic dynamics and the financial system of Rubiataba was also carried out with the public agencies of this municipality. Data from the State Department of Planning and Development and institutes such as IBGE, IPEA, IMB and the National Treasury Secretariat were used. Questionnaires were applied to health institutions, education, public agencies and retail establishments, and interviews were conducted with local authorities, secretaries, traders, workers, employees and students. Questionnaires were carried out in the city's commerce, agricultural houses, industry in the upholstery sector and also in the alcohol and sugar production industry, called Cooper Rubi and Agro Rubi. The study presented here is divided into three chapters outlining the study object. In the first chapter the processes of territorial formation of Rubiataba were analyzed, being pointed the main factors of population and urbanization of the Goian territory, the influences of the Getúlio Vargas government with the policy of March to the West in the formation of the municipality of Rubiataba and the aspects of settlement in the origins of the municipality. In the second chapter, we intend to highlight general aspects of this municipality, emphasizing the main territorial elements of its urban nucleus, such as public health and education agencies, as well as the retail trade, seeking to understand the current socio-spatial conjuncture of this urban space. Next, a discussion was carried out involving the rural and urban space in the city of Rubiataba with the purpose of consolidating it as an urban space, based on a theoretical foundation aimed at understanding this city as a socially produced urban space. In the third chapter, aspects related to the urban morphology of the city and its socioeconomic dynamics were analyzed, analyzing its functionalities within the intraurban space, through a thorough reading and the own research in the city (interviews, observation, description and analysis of this urban space ), it was possible to establish characteristics of its spatial organization, in addition to establishing the set of influences established by this municipality. Also, a brief characterization of space and subject will be dedicated at the last moment, emphasizing aspects such as daily life, leisure and religiosity, seeking to understand some particularities.